The Influence of Racket Sports on Longevity and Comprehensive Health Benefits - Adrianna Dylik; Łukasz Krawczak; Hanna Gulaczyk; Maria Spychalska; Jan Spychalski; Mikołaj Musiał; Mikołaj Kaczmarek; Wiktoria Grochowska; Weronika Gryczyńska (Quality in Sport)
​​Introduction and aim: Physical activity is one of the key components of human life, essential for maintaining health. Racket sports, which emphasize endurance and coordination while engaging a larger number of participants, are increasing in popularity. The aim of this work is to analyze the impact of racket sports on human health in comparison to individual sports.